The Influence of Profit Sharing on Profitability in Islamic Banking : (Case Study at Bank BCA Syariah in 2021) - Zulfikar Hasan (Eastasouth Institute, 2022)
This analysis aims to define the extent of the influence of the level of profit sharing on profitability, which takes a case study at Bank BCA Syariah in 2021. The author takes the title of this research for reasons of interest in the differences and consequences of Islamic Banking in Indonesia which has gradually evolved into a powerful competitor for conventional banks. If you look at data, which has undergone substantial growth since 2019, it becomes an attraction for the author to take the title of this research. In this study, the authors collect data through the literature study method, which comes from Bank BCA Syariah's financial information. This study aims to confine the capacity of the impact of the level of profit sharing on profitability. The upshots of this analysis are profit sharing has no significant influence on profitability.